RASIO KEUANGAN DAN UKURAN PERUSAHAAN DALAM MEMPREDIKSI KEBIJAKAN DIVIDEN - Sri Sudarsi; Ika Rosyada Fitriati; Andi Kartika (STIE Pelita Nusantara Semarang, 2021)
This research aims to provide the empirical evidence of financial ratios and the company size in predicting the dividend policy. The research object was carried out on banking companies that listed on the Indonesian stock exchange for the 2014-2018 period. The sample selection was carried out using the proposive sampling method, in which the sample selection used certain criteria, and obtained a sample of 210 companies. Data analysis techniques using the multiple linear regression. The results of this research prove that the profitability ratio has a positive and significant effect on the dividend policy, the company size has a positive and significant effect on the dividend policy, while liquidity has no effect on the dividend policy.